2007
DOI: 10.1899/0887-3593(2007)26[232:eciall]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Epilithic communities in a lake littoral zone: the role of water-column transport and habitat development for dispersal and colonization of meiofauna

Abstract: During the past 30 y, periphyton has been recognized as a key component in the benthos of lake littoral zones. However, the role of meiofauna-sized organisms living in the periphyton and mechanisms regulating and influencing those communities largely have been neglected, and the process of community development and colonization pathways of periphytic meiofauna are unknown in lakes. We studied these processes on littoral hard substrates in an oligotrophic lake. We manipulated the access of meiofauna to artifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 61 publications
2
24
0
2
Order By: Relevance
“…The tiles introduced into the newly-prepared and filled control mesocosm represented newly-inundated reservoir littoral. The experimental timeframe for measuring growth of inundated littoral followed previous estimates from colonization experiments, which have shown that a plateau in algal community development was reached after three weeks [26]. Consequently, the experimental period of 5 weeks ensured that we observed the loss of a natural benthic algal community.…”
Section: Experimental Designmentioning
confidence: 95%
See 1 more Smart Citation
“…The tiles introduced into the newly-prepared and filled control mesocosm represented newly-inundated reservoir littoral. The experimental timeframe for measuring growth of inundated littoral followed previous estimates from colonization experiments, which have shown that a plateau in algal community development was reached after three weeks [26]. Consequently, the experimental period of 5 weeks ensured that we observed the loss of a natural benthic algal community.…”
Section: Experimental Designmentioning
confidence: 95%
“…To approximate realistic WLF as the treatment, we applied fluctuations that were previously found to be the most common in terms of frequency and amplitude in alpine reservoirs in the Swiss Alps [5]: a 12 h period of emptying and filling, respectively; with an amplitude of 40 cm corresponding to half the filling level of 80 cm. White square ceramic tiles (10 cm by 10 cm) were used as a standardized substrate because of the unified, easy-to-sample area, homogenous albedo and uniform angle towards the water surface [26]. Five tiles were placed in rows each 10 cm from the water surface (45 tiles × 2 mesocosms).…”
Section: Experimental Designmentioning
confidence: 99%
“…Mas essas características gerais, que corroboram a teoria de biogeografia de ilhas, também dependem do grau de maturidade e complexidade das associações dos vizinhos doadores de espécies; se são dominados por oportunistas generalistas ou especialistas (AZOVSKY, 1988). Neste contexto, isolamento em pequenas lagoas ou massas de águas costeiras pode ser de relevância estrutural para as comunidades de meiofauna (PETERS et al, 2007). Em longo prazo, isso pode conduzir à deriva genética das populações (PETERS et al, 2007).…”
Section: Distúrbio E Recolonizaçãounclassified
“…Neste contexto, isolamento em pequenas lagoas ou massas de águas costeiras pode ser de relevância estrutural para as comunidades de meiofauna (PETERS et al, 2007). Em longo prazo, isso pode conduzir à deriva genética das populações (PETERS et al, 2007).…”
Section: Distúrbio E Recolonizaçãounclassified
“…Another common strategy is to spawn soon after a rise in water level (Gafny et al 1992;Ali and Kadir 1996;Ozen and Noble 2002) because no biofilm has yet developed on freshly inundated substrata. Because periphytic biofilm can develop within 14 days or less (Gafny et al 1992;Peters et al 2007), the window of opportunity in which fishes that spawn in shallow water can benefit from biofilm-free substrata is narrow.…”
Section: Introductionmentioning
confidence: 99%